STRATEGI PENGEMBANGAN KAPASITAS PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA REGIONAL BANDUNG PADA ERA HUMAN CAPITAL MANAGAMENT - Suparjana, Suparjana (Journal of Innovation Research and Knowledge, 2024)
This paper is a theoretical and best practices review regarding the consequences of four disruptions, which are : the shift of Human resources paradigm to Human capital Management, the difussion of Information and communication technology and VUCA ( Volatility, Uncertainty,Complexity and Ambiguity) World and Pandemic Covid-19 deases on the need of training agency to transform their institution and Compentency Development Model for Civil Servant/ASN at Center of Human Resouces Development Board Chapter Bandung (PPSDM Regional Bandung), Minsitry od Home Affair, Republic of Indonesia. It’s a general known that since the last decade, the human resources management policy for civil servant/ASN has changed significantly. Competency development of Civil servant/ASN need to be improved due to the drastic change of strategic environments both internal and external, which are: the difussion of Information, communication and Technology as well as needs of public service quality for the citizen The shift in the Human Resources/HR management paradigm from the Human Resources Management/HRM paradigm to Human Capital Management/HCM, encourages PSDM Regional Bandung to transform capacity development strategies which include institutional aspects, management systems, work culture, strategy. and Bangkom and HR training methods and network strengthening, so that competency ddevelopment proram can be implemented efficiently, effectively, innovatively and integrated.Base on research, PPSDM Regional Bandung needs to develop capacity in term of Institution, System Management and Individual dimension in integrated and sistematically . In order to transform methods, model and strategy of capacity development for civil servant, PPSDM Regional Bandung promote and apply SMART ( Strategic Learning, Mothod-Modern, Ambience, Role Model and Technique). This strategy is an effective step to adapt and accelerate the development of today's very dynamic and complex strategic environment. At the same time, strengthening collaboration between stakeholders has become a necessity that cannot be postponed any longer